Business valaution - Pegas Nonwovnes SA - Mihardja, André (2008)
This thesis concerns valuation of Pegas Nonwovens SA. The valuation was carried out using DFC entity method and market comparable approach. The valuation also contains financial analysis of the company, market analysis and projected financial statements and value drivers.